2015
DOI: 10.4253/wjge.v7.i17.1250
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of cold snare polypectomy in Japan: A pilot study

Abstract: CSP is feasible in Japan. However, immediate bleeding, retrieval failure and uncertain assessment of the lateral tumor margin should not be underestimated. Careful endoscopic diagnosis before and evaluation of the tumor residue after CSP are recommended when implementing CSP in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 25 publications
3
89
4
Order By: Relevance
“…Kim et al[11] also demonstrated that the overall complete resection rate was significantly higher in the CSP group than in the CFP (96.6% vs 82.6%, P = 0.01) for polyps ≤ 7 mm. Authors of a pilot study conducted in Japan reported that the rate of complete resection after CSP for polyps < 10 mm was 60%[3]. The present study’s findings showed that the overall complete resection rate for polyps 3-5 mm was significantly higher with CSP than with HFB, although six polyps in the CSP group could not be evaluated because they broke into pieces in the working channel of the scope during aspiration.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Kim et al[11] also demonstrated that the overall complete resection rate was significantly higher in the CSP group than in the CFP (96.6% vs 82.6%, P = 0.01) for polyps ≤ 7 mm. Authors of a pilot study conducted in Japan reported that the rate of complete resection after CSP for polyps < 10 mm was 60%[3]. The present study’s findings showed that the overall complete resection rate for polyps 3-5 mm was significantly higher with CSP than with HFB, although six polyps in the CSP group could not be evaluated because they broke into pieces in the working channel of the scope during aspiration.…”
Section: Discussioncontrasting
confidence: 47%
“…Cold snare polypectomy (CSP) is becoming a common method for resecting small or diminutive polyps without using submucosal injections or electrocautery, and it is regarded as a safe treatment in Western countries[2]. Recently, it has also gradually gained popularity in Japan[3-5]. The advantages of CSP are that electrocautery-related damages to the submucosal vascular tissue are prevented and there are fewer restrictions on patients’ postoperative activity or diet.…”
Section: Introductionmentioning
confidence: 99%
“…Because, complete removal of the entire mucosal layer is important to avoid recurrence after CSP for small cancers invading the muscularis mucosa, which can be completely removed with endoscopic mucosal resection following submucosal injection. 5 Regarding the high incomplete mucosal layer resection rate (63%), CSP should be used for intra-epithelial lesions only, and careful pretreatment examination is mandatory, even for subcentimeter polyps. Although the incidence of muscularis mucosa residue with CSDP was similar to previous reports and significantly higher than that without CSDP, we believe that a 57% incomplete mucosal layer resection rate is still considerably high.…”
Section: Discussionmentioning
confidence: 99%
“…In general, CSP is done for benign polyps <10 mm in diameter without a high‐frequency device, and is associated with a low risk of complications; including postoperative hemorrhage . Compared to standard polypectomy, CSP has been reported as a safe procedure even in patients taking warfarin . Furthermore, the procedural time is significantly shorter with CSP than with standard polypectomy …”
Section: Introductionmentioning
confidence: 99%